Interface structure and shear strength of brazed joints between cermets and 45 steel in formed Cu-Zn-Ni-Mn-Si-Mo filler metal. Issue 1 (2nd January 2023) - Xue, Chaogang; Zheng, Yong; Lu, Xuepeng; Xu, Xiangyu; Han, Zishen; Yang, Huimin; Li, Xiaoyu; Zhu, Xinggen
Abstract: In this study, brazing joints between cermets and 45 steel were obtained by vacuum brazing, using the self-prepared Cu-Zn-Ni-Mn-Si-Mo filler metal with appropriate melting point and good wettability on cermets. The influences of brazing temperature and holding time on the shear strength of Mo2 FeB2 -based cermets and Ti(C, N)-based cermets/filler metal/45 steel joints were evaluated. Results revealed that as the brazing temperature increased or the holding time prolonged, the shear strength of both joints first increased and then decreased. The maximum shear strength of 270.4 MPa was achieved for the joint between Ti(C, N)-based cermets and 45 steel brazed at 1080 °C for 15 min, while the maximum shear strength of 275.7 MPa was recorded between Mo2 FeB2 -based cermets and 45 steel brazed at 1040 °C for 15 min. Moreover, the interface structure of brazing joints was observed and characterized under optimal technological parameters by SEM and EDS. The diffusion layer with a certain thickness was formed at the interface, and thus the joints were composed of five areas: 45 steel, transition layer, metal filler, transition layer, and cermets. Elements diffused from the filler metal to the base metal on both sides, resulting in the improvement of the shear strength of the joints.